Bi metal-modified Bi4O5I2 hierarchical microspheres with oxygen vacancies for improved photocatalytic performance and mechanism insights. Issue 16 (28th July 2017) - Liu, Xiufan; Xiong, Xuyang; Ding, Shuoping; Jiang, Qingqing; Hu, Juncheng
Abstract : In this work, we firstly synthesized metallic Bi-modified Bi4 O5 I2 nanocomposites with oxygen vacancies via a facile one-pot solvothermal method. Abstract : In this work, we firstly synthesized metallic Bi-modified Bi4 O5 I2 nanocomposites with oxygen vacancies via a facile one-pot solvothermal method. The deposited Bi metal and oxygen vacancies endowed the Bi/Bi4 O5 I2 samples with dramatically enhanced photocatalytic performance for degradation of bisphenol A (BPA) and methyl orange (MO) under visible light irradiation. In particular, the improved photocatalytic activity can be ascribed to the synergistic effect of Bi metal and oxygen vacancies, which resulted in their efficient light harvesting properties and excellent charge separation ability. The photocatalytic mechanism of Bi/Bi4 O5 I2 for organics degradation was demonstrated. This work could shed light on exploring high photocatalytic performance materials and stimulating the development of non-noble metal/Bi x O y I z photocatalysts, which would also contribute to advancement in environmental remediation and energy exploitation.